The economic and fiscal impact of incremental use of cell-based quadrivalent influenza vaccine for the prevention of seasonal influenza among healthcare workers in Italy - Giovanna Elisa Calabrò; Filippo Rumi; Roberto Ricciardi; Americo Cicchetti (BMC, 2024)
Abstract Background Seasonal influenza has a significant impact on public health, generating substantial direct healthcare costs, production losses and fiscal effects. Understanding these consequences is crucial to effective decision-making and the development of preventive strategies. This study aimed to evaluate the economic and the fiscal impact of implementing an incremental strategy for seasonal influenza prevention using the cell-based quadrivalent influenza vaccine (QIVc) among healthcare workers (HCWs) in Italy. Methods To estimate the economic impact of implementing this strategy, we performed a cost analysis that considered direct healthcare costs, productivity losses and fiscal impact. The analysis considered a 3-year time horizon. A deterministic sensitivity analysis was also conducted. Results Assuming a vaccination coverage rate of 30% among HCWs, the analysis considered a total of 203 018 vaccinated subjects. On analysing the overall differential impact (including direct costs, indirect costs and fiscal impact), implementing QIVc vaccination as a preventative measure against influenza among HCWs in Italy would yield societal resource savings of €23 638.78 in the first year, €47 277.56 in the second year, and €70 916.35 in the third year, resulting in total resource savings of €141 832.69. Conclusions The study demonstrated that implementing the incremental use of QIVc as part of a preventive strategy for seasonal influenza among HCWs in Italy could yield positive economic outcomes, especially in terms of indirect costs and fiscal impact. The resources saved could be utilized to fund further public health interventions. Policy-makers should consider these findings when making decisions regarding influenza prevention strategies targeting HCWs.